2020
DOI: 10.1002/rmb2.12348
|View full text |Cite
|
Sign up to set email alerts
|

The impact of endometrial injury on reproductive outcomes: results of an updated meta‐analysis

Abstract: Implantation success following in vitro fertilization (IVF) relays on several factors, including embryonic quality and endometrial receptivity. 1,2 Repeated implantation failure (RIF) after IVF and embryo transfer (ET) is a frequent problem many patients struggle with. Two definitions of RIF are acceptable in the academic and clinical fields. The recent definition refers to RIF as failure to achieve a pregnancy after transferring at least four good-quality embryos in a minimum of three cycles in a woman under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
(211 reference statements)
0
7
0
4
Order By: Relevance
“…In literature review, it can be observed that the effect of local endometrial injury on pregnancy outcomes has mostly been investigated in ART (assisted reproductive technology) cycles. In the meta-analysis of Nahshon C. et al including 3016 cases from 17 randomized controlled studies (RCT), in women with at least one previous failed cycle, the effect of local endometrial injury on IVF outcomes was evaluated and CPR (RR 1.19 [95% CI 1.06-1.32]) and LBR (live birth rate) (RR 1.18 [95%CI 1.04-1.34]) were found to be significantly improved after local endometrial injury (22). However, in the meta-nalysis of Van Hoogenhuijze et al including 14 RCT with 2537 participants, the effect of local endometrial injury in patient groups with a previous failed full IVF/ICSI cycle was evaluated and no difference was found between study and control groups with regard to LBR (RR 1.01 [95%CI 0.68-1.51]) and CPR (RR 1.04 [95%CI 0.74-1.45]) (23).…”
Section: Discussionmentioning
confidence: 99%
“…In literature review, it can be observed that the effect of local endometrial injury on pregnancy outcomes has mostly been investigated in ART (assisted reproductive technology) cycles. In the meta-analysis of Nahshon C. et al including 3016 cases from 17 randomized controlled studies (RCT), in women with at least one previous failed cycle, the effect of local endometrial injury on IVF outcomes was evaluated and CPR (RR 1.19 [95% CI 1.06-1.32]) and LBR (live birth rate) (RR 1.18 [95%CI 1.04-1.34]) were found to be significantly improved after local endometrial injury (22). However, in the meta-nalysis of Van Hoogenhuijze et al including 14 RCT with 2537 participants, the effect of local endometrial injury in patient groups with a previous failed full IVF/ICSI cycle was evaluated and no difference was found between study and control groups with regard to LBR (RR 1.01 [95%CI 0.68-1.51]) and CPR (RR 1.04 [95%CI 0.74-1.45]) (23).…”
Section: Discussionmentioning
confidence: 99%
“…Olguların gruplara göre demografik özellikleri. (9). Uygulamanın etkinliğinin belirgin olabileceği optimal popülasyon ve uygulama şeklinin halen tam bilinmediği ve tartışmalı olduğu bildirilmiştir (9).…”
Section: H/s Ve Endometrial Biyopsi Sonuçlarıunclassified
“…(9). Uygulamanın etkinliğinin belirgin olabileceği optimal popülasyon ve uygulama şeklinin halen tam bilinmediği ve tartışmalı olduğu bildirilmiştir (9). Yakın zamanda yayınlanan retrospektif bir çalışmada en az iki IVF siklusu sonrası (ortalama 4,5 siklus) açıklanamayan tekrarlayan implantasyon başarısızlığı olan olgularda IVF öncesi geç proliferatif ve orta luteal fazda pipelle endometrial hasar oluşturmanın uygulama yapılmayan kontrollere göre klinik gebelik ve canlı doğum oranlarında anlamlı oranda artışla ilişkili bulunduğu ve uygulamanın gebelik oluşması üzerine bağımsız bir faktör olabileceği öne sürülmüştür.…”
Section: H/s Ve Endometrial Biyopsi Sonuçlarıunclassified
See 2 more Smart Citations